Livestock manure valorization to biochemicals and energy using CO2: A case study of goat excreta. (March 2019) - Kim, Youkwan; Jeon, Young Jae; Yim, Jun-Ho; Jeong, Kwang-Hwa; Park, Young-Kwon; Kim, Taejin; Lee, Jechan; Kwon, Eilhann E.
Highlights: Valorization of livestock manure to chemicals and energy. Use of livestock manure as an initial feedstock for the biorefinery. Furfural production via the acid-catalyzed dehydration of livestock manure. Sustainable pyrolytic platform using CO2 as reactive gas medium. Abstract: Furfural has been considered a potential feedstock of biofuels and biopolymers. As a waste-to-resource opportunity, this study focused on the valorization of goat excreta to obtain furfural and recover energy in the form of pyrolytic gas that helps increase thermochemical process efficiency. Three feedstocks (goat excreta, rice straw, and corncob) were compared to verify whether goat excreta is a promising feedstock of furfural. The furfural concentration from goat excreta (3.2 g L −1 ) via acid-catalyzed dehydration was comparable to that from rice straw or corncob. To maximize energy recovery from goat excreta via pyrolysis, CO2 was employed as a reactive medium (compared with typical pyrolysis with N2 ). This study experimentally proved that CO2 plays a pivotal role in shifting carbon distribution from pyrolytic oil to pyrolytic gas, thereby enhancing the generation of CO (the main component of pyrolytic gas). Based on the experimental results, it is suggested that goat excreta can be a promising initial feedstock for the production of furfural and energy recovery.